Creel survey and economic assessment of the walleye fishery in Pool 9 on the Upper Mississippi River during 1983-1984 - Ferkin, Gary (My University, 1986)
A creel survey of walleye was conducted in Pool 9 of the Upper Mississippi River from June 1, 1983 through May 31, 1984 to assess the walleye harvest and to estimate the economic impact of the walleye fishery to the area. Estimated annual walleye fishing expenditures in the pool approached 1.2 million dollars. The projected dollar value of walleye angler's boats, motors, and boat accessories in Pool 9 was an additional $1,066,740. Nearly 30,000 angler tips were made during the year in the pool by walleye fishermen. Walleye anglers fished an estimated 104,515 man-hours (mh) or 43 mh/ha/yr, heavy by regional standards. The average catch rate for walleye during 1983 and 1984 was relatively high at 1.05 fish/mh. The total estimated harvest was 130,086 fish, or 53 fish/ha. The estimated weight of the total harvest was 94,585 kg or 38.8 kg/ha, high by regional standards. A total of 135 walleyes was sampled from the creel survey during 1983 for age and growth determinations. The total length-weight relationship was expressed by the equation log W= -6.3000 + 3.4876 log TL. Mean condition factors for walleye by size ranged from 0.68 to 1.11, and averaged 0.96. Age and growth calculations were determined from the annuli method using scales and dorsal fin spines. The estimated back-calculated total lengths of walleye using the scale method at annuli I through VI were determined to be 179, 305, 401, 477, 519, and 564 mm, respectively. Similar data were obtained from analyses of dorsal fin spines. The walleye growth rate in Pool 9 was favorable when compared to growth rates from several other waters. The average size of walleye harvested during the year was 406 mm and 727 g. Approximately 15% of the walleyes creeled and harvested by anglers were less than 330 mm (13 in). Nearly 75% of the walleyes harvested under 330 mm occurred in the tail waters of Lock and Dam 8 during the spring and fall seasons. However, there appears to be no biological basis for implementing a minimum size limit.
Keywords: Mississippi River; Walleye fishing; Walleye (Fish)